Pelaksanaan Praperadilan Yang Diajukan Oleh Pihak Ketiga Terhadap Penghentian Penyidikan Oleh Jaksa Penuntut Umum Dalam Tindak Pidana Korupsi (Studi Kasus Pengadilan Negeri Boyolali) - Saputra, Nanda Fenta; , Hartanto, S.H., M.Hum; , Marisa Kurnianingsih S.H.,M.Kn (2016)
This study aims to determine the concideration of the public prosecutor in the termination of the casw and to invetigation the implementation of the proposed pretrial third parties about the termination of the investigation by the public prosecutor. The results showed that consederation of the public prosecutor in the termination of the investigation of corruption case pretrial an act of termination of the investigation, the views from the investigation process stalled or stopped many years. Implementation of the proposed pretrial third parties about the termination of the investigation by the public prosecutor in the corruption that runs smoothly and in compliance with the prinsiples of fair trial and impartial. Barriers experienced by a third party that the submission should disposition by the chairman of the court, interested third parties unknown to the law enforcement apparatus and the prosecution passive.